2019
DOI: 10.1111/eva.12803
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for adaptive responses to historic drought across a native plant species range

Abstract: As climatic conditions change, species will be forced to move or adapt to avoid extinction. Exacerbated by ongoing climate change, California recently experienced a severe and exceptional drought from 2011 to 2017. To investigate whether an adaptive response occurred during this event, we conducted a “resurrection” study of the cutleaf monkeyflower ( Mimulus laciniatus ), an annual plant, by comparing trait means and variances of ancestral seed collections (“pre‐drought”) with contempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 111 publications
3
60
1
1
Order By: Relevance
“…A decrease in SLA may occur in response to drought in herbaceous leaves as a result of an increased investment in structural tissues allowing increased resistance to unfavorable environmental conditions (Maroco et al, 2000;Chaves et al, 2003). This trait has been widely used in experiments with different water availability regimes both for the comparison of populations within a species, and comparisons between two or more species since it plays an important role in linking plant carbon and water cycles (Marron et al, 2003;Xu and Zhou, 2008;Grassein et al, 2010;Lázaro-Nogal et al, 2015;Wellstein et al, 2017;Dickman et al, 2019). Therefore, our results suggest that S. hookeri, which had lower SLA than S. grahamii, appears to show greater dehydration tolerance than S. grahamii.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in SLA may occur in response to drought in herbaceous leaves as a result of an increased investment in structural tissues allowing increased resistance to unfavorable environmental conditions (Maroco et al, 2000;Chaves et al, 2003). This trait has been widely used in experiments with different water availability regimes both for the comparison of populations within a species, and comparisons between two or more species since it plays an important role in linking plant carbon and water cycles (Marron et al, 2003;Xu and Zhou, 2008;Grassein et al, 2010;Lázaro-Nogal et al, 2015;Wellstein et al, 2017;Dickman et al, 2019). Therefore, our results suggest that S. hookeri, which had lower SLA than S. grahamii, appears to show greater dehydration tolerance than S. grahamii.…”
Section: Discussionmentioning
confidence: 99%
“…Using this approach, researchers can directly quantify evolutionary response to environmental change [314,315]. For example, studies resurrecting stored seeds, have shown rapid evolution of earlier flowering or seedling emergence following drought [80,[316][317][318] and warming [319], directional and/or stabilizing selection on flowering time in response to changes in precipitation patterns [80,320], rapid evolution of phenotypic plasticity in an invasive species [321], and evolution of herbicide resistance [322].…”
Section: Detecting Contemporary Evolutionmentioning
confidence: 99%
“…These shifts have involved local extinctions and population contractions at the warmer range edges as well as range expansions into historically cooler regions at poleward latitudes and upslope elevations (Angert et al, 2011;Chuang & Peterson, 2016;Sheth & Angert, 2018;Anderson & Wadgymar, 2020). Additionally, many species now emerge and reproduce significantly earlier in the year, which is likely a biological response to shortened winters, earlier onset of the growing season, and prolonged droughts (Cook et al, 2012;CaraDonna et al, 2014;Hamann et al, 2018;Wadgymar et al, 2018;Dickman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%